FENOMENA KEBERADAAN WARUNG TENDA JALANAN DALAM MENGGERAKKAN PEREKONOMIAN MASYARAKAT (STUDI KASUS WARUNG TENDA DIJALAN PEJANGGIK CAKRANEGARA KOTA MATARAM) - rendi oktasari; Hery Astika Putra (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2020)
This research is entitled "The Phenomenon of the Occasion of Street Tent Stalls inMobilizing the Economy of the society (Study Case of Street Tent Stall on Pejanggik street,Cakranegara, Mataram)". The purpose of this research is to find out the size of the incomeof the people who open tent stalls on the street of the beekeepers on pejanggik street,cakranegara, Mataram, find out what things affect the income, production costs, menusproduced and how to market them.The type of research used in this study is a qualitative research with a phenomenonapproach, using interviews and direct observation as a technique of the data collection, theinformants of this study consisted of tent stall owners, tent stall employees, people who sellaround the tent stalls and ordinary people in the pejanggik street of Cakaramegara.The results of this study indicate that the income generated from the tent shopbusiness is quite large on average Rp. 9,000,000 evert month, also able to open jobvacancies that can reduce unemployment. On the other hand the presence of this tent stall isable to improve the standard of living of people who sell around the tent stalls such as thoseselling martabak and terang bulan, cigarettes, fried foods, juices, cakes whose averageincome is Rp. 200,000 to Rp. 400,000 every day and able to be an attraction for thecommunity to open the same business, especially in the culinary field.